2016
DOI: 10.1016/j.fsi.2016.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional characterization of Toll-like receptor (Tlr)1 and Tlr2 in common carp ( Cyprinus carpio )

Abstract: Toll-like receptors (TLRs) are fundamental components of innate immunity that play significant roles in the defence against pathogen invasion. In this study, we present the molecular characterization of the full-length coding sequence of tlr1, tlr2a and tlr2b from common carp (Cyprinus carpio). Each is encoded within a single exon and contains a conserved number of leucine-rich repeats, a transmembrane region and an intracellular TIR domain for signalling. Indeed, sequence, phylogenetic and synteny analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…In mammals, TLR1 is involved in the recognition of triacylated lipoproteins and mycobacterial products by binding to TLR2 to form a heterodimer ( 157 ). Teleost TLR1 and TLR2 have been characterized in Tetraodon ( Tetraodon nigroviridis ) ( 157 ), pufferfish ( Takifugu rubripes ) ( 158 ), zebrafish ( Danio rerio ) ( 159 , 160 ), Japanese flounder ( Paralichthys olivaceus ) ( 161 ), channel catfish ( Ictalurus punctatus ) ( 152 , 162 ), rainbow trout ( Oncorhynchus mykiss ) ( 163 , 164 ), orange-spotted grouper ( Epinephelus coioides ) ( 165 ), large yellow croaker ( Pseudosciaena crocea ) ( 166 168 ), rohu ( Labeo rohita ) ( 169 ), common carp ( Cyprinus carpio ) ( 170 ), and grass carp ( Ctenopharyngodon idella ) ( 171 ). TLR2 signaling plays an important role in the activation of intestinal immune system in mammals ( 172 ).…”
Section: Tlrs In Non-mammalian Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, TLR1 is involved in the recognition of triacylated lipoproteins and mycobacterial products by binding to TLR2 to form a heterodimer ( 157 ). Teleost TLR1 and TLR2 have been characterized in Tetraodon ( Tetraodon nigroviridis ) ( 157 ), pufferfish ( Takifugu rubripes ) ( 158 ), zebrafish ( Danio rerio ) ( 159 , 160 ), Japanese flounder ( Paralichthys olivaceus ) ( 161 ), channel catfish ( Ictalurus punctatus ) ( 152 , 162 ), rainbow trout ( Oncorhynchus mykiss ) ( 163 , 164 ), orange-spotted grouper ( Epinephelus coioides ) ( 165 ), large yellow croaker ( Pseudosciaena crocea ) ( 166 168 ), rohu ( Labeo rohita ) ( 169 ), common carp ( Cyprinus carpio ) ( 170 ), and grass carp ( Ctenopharyngodon idella ) ( 171 ). TLR2 signaling plays an important role in the activation of intestinal immune system in mammals ( 172 ).…”
Section: Tlrs In Non-mammalian Vertebratesmentioning
confidence: 99%
“…Searches for reptilian TLR sequences have identified these in only one species, the green anole lizard Anolis carolinensis , which have been annotated as molecules resembling mammalian TLR2, 3, 4, 5, 6, 7, and 13. Recently, Voogdt and colleagues ( 170 ) reported the cloning, characterization, and functional analysis of TLR5 from A. carolinensis , and found that the receptor (acTLR5) displays a typical TLR protein structure with 22 extracellular LRRs flanked by N- and C-terminal LRR domains, an intracellular TIR domain, and a transmembrane region. Phylogenetically, acTLR5 is most distant from the TLR5 of fish and closest to the avian TLR5.…”
Section: Tlrs In Non-mammalian Vertebratesmentioning
confidence: 99%
“…Common carp ( Cyprinus carpio L.) is a freshwater fish widespread in Europe and Asia. To date, TLR1 and TLR2 [ 19 , 20 ], TLR3 [ 21 ], TLR4 [ 22 ], TLR9 [ 23 ], TLR18 [ 24 ], TLR20 [ 25 ] and TLR22 [ 26 ] were reported in common carp. Since TLRs play an important role in host anti-pathogen responses, the study of TLRs will be beneficial to the disease control of common carp.…”
Section: Introductionmentioning
confidence: 99%
“…For reasons unknown, TLR10 has been preserved in some mammals (including humans) and has been lost in other vertebrates. Among teleost fish, the common carp ( Cyprinus carpio ) duplicated its TLR2 gene ( 11 ), whereas the Atlantic cod ( Gadus morhua ) lost TLR1, TLR2, TLR6, and TLR10 altogether ( 12 ). In birds, duplications of TLR1 and TLR2 are abundant ( 6 , 13 ) which has left chicken ( Gallus gallus ) with the paralogs TLR2A, TLR2B, TLR1A (also known as TLR16), and TLR1B.…”
Section: Introductionmentioning
confidence: 99%